CHARACTERISTICS AND IMPORTANCE OF MICRO-HYDROPOWER PLANTS DESIGNED FOR LOW-PRESSURE FLOWS - Ismoilov Muslimbek Murodjon o‘g‘li (World Scientific Research Journal, 2025)
Abstract: Micro-hydroelectric power plants (micro-hydropower plants) are power generation systems optimized for operation in low-pressure flows. This technology is designed to operate in small and medium-sized rivers or canals. Micro-hydropower plants are important as an efficient use of natural energy and an environmentally friendly source of energy. In this article, we will provide detailed information about micro-hydropower plants operating in low-pressure flows.